Women's Zionism worldwide, 1897-1948 - Ḳatsburg-Yungman, Mirah ca. 20./21. Jh. (Berghahn, 2025)
"Offering the first comprehensive historiographic exploration of women's roles in the Zionist movement worldwide, this geographically wide-ranging study explores the ideologies, goals, strategies, activities, accomplishments and failures of women's organizations and individuals in Europe, the United States, Latin America, the Middle East, and North Africa. Covering the period from the inception of Zionism to the founding of Israel, this volume sheds light on how women's unique mode of Zionism differed from that of men and how it influenced the Jewish community in Mandatory Palestine, in Israel, and the Zionist movement as a whole"-- Provided by publisher